Temperature-sensitive mutations in the bacteriophage Mu c repressor locate a 63-amino-acid DNA-binding domain. - Vogel, J L (1991)
Phage Mu's c gene product is a cooperative regulatory protein that binds to a large, complex, tripartite 184-bp operator. To probe the mechanism of repressor action, we isolated and characterized 13 phage mutants that cause Mu to undergo lytic development when cells are shifted from 30 to 42 degrees C. This collection contained only four mutations in the repressor gene, and all were clustered near the N terminus. The cts62 substitution of R47----Q caused weakened specific DNA recognition and altered cooperativity in vitro. A functional repressor with only 63 amino acids of Mu repressor fused to a C-terminal fragment of beta-galactosidase was constructed. This chimeric protein was an efficient repressor, as it bound specifically to Mu operator DNA in vitro and its expression conferred Mu immunity in vivo. A DNA looping model is proposed to explain regulation of the tripartite operator site and the highly cooperative nature of repressor binding.